If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = 38 + -4x Reorder the terms: -7 + 5x = 38 + -4x Solving -7 + 5x = 38 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -7 + 5x + 4x = 38 + -4x + 4x Combine like terms: 5x + 4x = 9x -7 + 9x = 38 + -4x + 4x Combine like terms: -4x + 4x = 0 -7 + 9x = 38 + 0 -7 + 9x = 38 Add '7' to each side of the equation. -7 + 7 + 9x = 38 + 7 Combine like terms: -7 + 7 = 0 0 + 9x = 38 + 7 9x = 38 + 7 Combine like terms: 38 + 7 = 45 9x = 45 Divide each side by '9'. x = 5 Simplifying x = 5
| (7x-8)(5x+3)=0 | | 6x-54=-3x(x+45) | | 6(x-2)+18=72 | | 12x^3+16x^4= | | x-7=38-4x | | -9-6+(-2)-7= | | 9.875-3= | | 3(90-x)=2(180-x) | | 9.75-3= | | 5x^2+65x+200= | | 9.5-3= | | 9+9r-2=9r+35-7r | | 20x+2= | | 5x+3=-129-6x | | 9.25-3= | | 4-3x=1-2x-1 | | 10x^2-15x-5=0 | | 5x+3=129-6x | | 15x+4=-15x-4 | | 5/x+4= | | 6x/5(3-5)=10x+7 | | 3x+5+9x-3=180 | | 12(3x-13)=96 | | -4+4p=2-2p | | -10.78=2.4k+4.1 | | x+3x-2=90 | | 3x-6=3x+12 | | x-6+7=20 | | 12x-3(x+4)=9x-9 | | 10r^2-16r+120=0 | | 5(9x-3)+11=7x-9 | | 2(t-5)+8t=5(2t+3)-9 |